Оцінка рівня податкового навантаження в регіоні (на прикладі Волинської області) - Цимбалюк, Ірина Олександрівна; Tsymbaliuk, I. O. (Хмельницький національний університет, 2013)
Розглянуто питання сутності та методики розрахунку податкового навантаження держави та регіону. Проведено розрахунок податкового коефіцієнта та здійснено оцінку рівня податкового навантаження Волинської області. The aim of the research is consists in working of the most widespread methodologies of estimation of the tax loading and feasible estimations of his level in the region. The Volyn area after the level of the financial providing is a grant, that conditioned by existence of low index of tax possibility, however, the analysis of tax revenues in a region testifies to the increase of their volume. The analysis of the tax situation in the region on the basis of comparison of tax revenues and contributions to the pension fund that paid by economic entities and population, showed that tax loading in the Volyn area is some less the all-Ukrainian level. However, the tax pressure on profits and incomes is vice versa higher of level of national index. These results testify to the proper level of tax payment physical persons in the Volyn area. At the same time, a difficult economic situation in a region and insufficient development of enterprise are negative factors, that influence fiscal efficiency of the tax system on this territory.
Estimation of level of the tax loading is in a region (on tne examle of the Volyn area)
Keywords: податкове навантаження; рівень податкового навантаження; податковий коефіцієнт; ефективна податкова ставка; tax burden; the level of tax burden; tax rate; the effective tax rate